Perbandingan Penatalaksanaan Fisioterapi Pada Dua Anak Dengan Cerebral Palsy Spastic Hemiplegia Sinistra - Dini Nur Alpiah; Katon Galih Wicaksono; Samuel Rolan Siregar; Tsabitah Ayu Nismara; Bunga Damayanti; Herana Herana; Maria Eno Rahayu Wibawaningrum (Universitas Pahlawan Tuanku Tambusai, 2026)
Cerebral Palsy (CP) is a permanent disorder of movement and posture development caused by a non progressive injury to the developing brain. The spastic type is the most common form of CP, and hemiplegic distribution is frequently encountered in pediatric physiotherapy practice. This case study aims to compare the assessment, physiotherapy diagnosis, intervention, and outcomes of two children diagnosed with Cerebral Palsy Spastic Hemiplegia Sinistra who have different clinical profiles. The first subject was a six year and two month old girl without comorbidities, while the second subject was a five year and one month old girl with microcephaly and epilepsy as comorbid conditions. Assessment used the Modified Ashworth Scale, range of motion measurement with a goniometer, and the Gross Motor Function Classification System. Results showed that the first subject was classified as GMFCS Level III with dominant spasticity in the left upper limb and an equinus gait pattern, while the second subject was classified as GMFCS Level IV with more extensive motor involvement and unstable postural control. After receiving physiotherapy consisting of range of motion mobilization, stretching, weight bearing exercises, and basic motor stimulation, both subjects showed progress at different rates. The subject without comorbidities progressed faster than the subject with neurological comorbidities. This study concludes that comorbid conditions such as microcephaly and epilepsy can worsen functional limitations in children with CP, so physiotherapy planning should be individually tailored to each child's clinical profile.